ANALISIS TERJEMAHAN PENANDA KOHESI PADA NOVEL DIARY OF A WIMPY KID: CABIN FEVER KARYA JEFF KINNEY KE DALAM BAHASA INDONESIA - Norma Noviana; M.R. Nababan; Riyadi Santosa (Universitas Sebelas Maret, 2017)
Background: The research aims to (1) identify the types of lexical cohesion taxonomic markers found in the novel Diary of a Wimpy Kid: Cabin Fever and its translation Diary si Bocah Tengil: Demam Kabin, (2) explain the shift of lexical cohesion taxonomic marker types found in the novel Diary of a Wimpy Kid: Cabin Fever and its translation Diary si Bocah Tengil: Demam Kabin, (3) identify and explain translation techniques in translating lexical cohesion taxonomic markers, (4) and explain the quality of lexical cohesion taxonomic markers in the novel based on accuracy and aceptability. Method: This descriptive qualitative research is an embeded case study, and oriented to translation product. The sources of this data consist of documents and informants (rater) selected with purpossive sampling technique. The document refers to the novel entitled Diary of a Wimpy Kid: Cabin Fever and its translation. The informants are six translation experts. The research data consist of (1) lexical cohesion taxonomic markers found in the novel Diary of a Wimpy Kid: Cabin Fever and its translation Diary si Bocah Tengil: Demam Kabin in the form of word and phrase, (2) the translation expert’s statements about the accuracy and aceptability level. The techniques of collecting data used in this research are document analysis, questionnares, and in-depth interview. The research data are analyzed using ethnography analysis which consisting of domain, taxonomy, and componential analysis until found a cultural theme. Result: The result shows that (1) there are ten types of lexical cohesion taxonomic markers which are categorized into hyponym, co-hyponym, conversion antonym, non-relational antonym, repetion (as a dominant cohesion type), close synonym, attitudinal synonym, consistency, cnstitution meronymy, and constitution co-meronymy, (2) there are shift in translating the lexical cohesion taxonomic marker types. It means the type of lexical cohesion taxonomic markes is different in the source language and in the target language, or it can be there is lexical cohesion taxonomic marker in source language but not in target language, or it cab be no lexical cohesion taxonomic marker in source language but there is lexical cohesion taxonomic marker in target language, (3) the translation techniques found in this research are established equivalent (as a dominant technique), variation, reduction, amplification, transposition, modulation, description, discursive creation, pure borrowing and naturalized borrowing. (4) The techniques applied to translation gives the good impact to quality of translation from accuracy and acceptability, supported with the high average score of quality. Keywords : lexical cohesion taxonomic, shift, translation techniques, translation quality